Development and initial evaluation of an instrument to assess physiotherapists' clinical reasoning focused on clients' behavior change. (4th May 2018) - Elvén, Maria; Hochwälder, Jacek; Dean, Elizabeth; Söderlund, Anne
ABSTRACT: Background and Aim : A systematically developed and evaluated instrument is needed to support investigations of physiotherapists' clinical reasoning integrated with the process of clients' behavior change. This study's aim was to develop an instrument to assess physiotherapy students' and physiotherapists' clinical reasoning focused on clients' activity-related behavior and behavior change, and initiate its evaluation, including feasibility and content validity. Methods : The study was conducted in three phases: 1) determination of instrument structure and item generation, based on a model, guidelines for assessing clinical reasoning, and existing measures; 2) cognitive interviews with five physiotherapy students to evaluate item understanding and feasibility; and 3) a Delphi process with 18 experts to evaluate content relevance. Results : Phase 1 resulted in an instrument with four domains: Physiotherapist; Input from client; Functional behavioral analysis; and Strategies for behavior change. The instrument consists of case scenarios followed by items in which key features are identified, prioritized, or interpreted. Phase 2 resulted in revisions of problems and approval of feasibility. Phase 3 demonstrated high level of consensus regarding the instrument's content relevance. Conclusions : This feasible and content-validated instrument shows potential for use in investigations of physiotherapy students' and physiotherapists' clinical reasoning, however continued development and testing are needed.